THE EFFECT OF TAX KNOWLEDGE, SERVICE TAX AUTHORITIES AND TAX PENALTIES FIRMNESS OF COMPLIANCE IN MEETING THEIR INCOME TAX LIABILITY WITH AN AWARENESS OF PAYING TAXES AS AN INTERVENING VARIABLE - Citra Ayu Noviana (Journal of Taxation Analysis and Review, 2019)
This study aims to determine (1) the effect of tax knowledge, service tax authorities and tax penalties against consciousness firmness pay income tax online shop owners, (2) the effect of tax knowledge, service tax authorities, tax penalties assertiveness and awareness of compliance obligations to pay taxes to the owner's income tax online shop, (3) the effect of tax knowledge, service tax authorities and tax penalties firmness against the owner of online shop compliance through awareness of paying taxes. This study uses survey and population are owners Online Shop Tokopedia.com sites. sampling using purposive sampling. The data used consist of primary data, which comes from distributing questionnaires to Own Online Shop listed in Tokopedia.com. Analysis of the data used is the analysis of SEM (Structural equating Modelling) with software version 2.0 SmartPLS M3. Results from this study are as follows: (1) knowledge of taxation and firmness sanctions respectively positive and significant impact on the consciousness of paying income tax online shop owners, (2) knowledge of taxation, tax penalties assertiveness and awareness to pay taxes each positive effect and significant compliance online shop owners, (3) knowledge of taxation and tax assertiveness respectively positive and significant effect on adherence owner of online shop through the consciousness of paying taxes, (4) the service tax authorities but not significant positive effect on consciousness or adherence, and (5) the service tax authorities but not significant positive effect on compliance through awareness.